2014
DOI: 10.5194/acpd-14-21785-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational estimates of detrainment and entrainment in non-precipitating shallow cumulus

Abstract: Abstract. Vertical transport associated with cumulus clouds is important to the redistribution of gases, particles and energy, with subsequent consequences for many aspects of the climate system. Previous studies have suggested that detrainment from clouds can be comparable to the updraft mass flux, and thus represents an important contribution to vertical transport. In this study, we describe a new method to deduce the amounts of gross detrainment and entrainment experienced by non-precipitating cumulus cloud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…The mass fractions of entrained air ( m e ) and detrained air ( m d ) gradually increase with increasing altitude, and this distribution is similar to the results of Norgren et al. (2016). The distribution of m e is consistent with previous studies (Ackerman, 1963; Cotton, 1975; Houze, 1993; M. ‐L.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mass fractions of entrained air ( m e ) and detrained air ( m d ) gradually increase with increasing altitude, and this distribution is similar to the results of Norgren et al. (2016). The distribution of m e is consistent with previous studies (Ackerman, 1963; Cotton, 1975; Houze, 1993; M. ‐L.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the results of Norgren et al. (2016), m d is much smaller than m e . Generally, m d is smaller than 50%, while m e varies from ∼0% to ∼80%.…”
Section: Calculation Of Gross Entrainment and Detrainmentsupporting
confidence: 91%
“…In this regard, observed detrainment levels are found to be strongly dependent on the updraft strength and the conditions in which that deep convection initiates and develops (e.g., Hartmann & Larson, 2002). Furthermore, estimates for the observed levels of maximum detrainment (as well as the net detrainment mass flux) are expected to vary significantly with convection type, size, and age (e.g., Barnes et al., 1996; Norgren et al., 2016). Previous studies (e.g., Takahashi & Luo, 2012) have argued that differences in the detrained outflow heights and the level of neutral buoyancy can act as a simple proxy for effective bulk convective entrainment.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid water content (LWC) must be larger than 0.001 g·m −3 and cloud droplet number concentration (N) must be greater than 10 cm −3 [22]. Given that the bulk-plume approach is only appropriate for developing clouds, the percentage of updraft within a cloud must exceed 80% [8] and the cloud penetration time must be longer than 5 s [11] to eliminate the clouds that are too small. There are a total of 156 clouds satisfying these criteria.…”
Section: Datamentioning
confidence: 99%
“…Besides the bulk-plume approach, Jensen and Del Genio [10] estimated λ in convective clouds using the vertical variation of potential temperature in cloud obtained from surface-based remote sensing data. Based on the conservation of cloud mass, total water content and moist static energy, Norgren et al [11] estimated the ratio of entrained mass to the total cloud mass and found that this ratio increased with height.…”
Section: Introductionmentioning
confidence: 99%